How the Digital Economy is Impacting the Indonesian MSMEs: Case of Tangsel and Lombok City - Suryani, Nining (Universitas Pamulang, 2024)
The marketing and the access to the capital are the main problem of MSME players in Tangsel City and Lombok City in Indonesia due to the lacking or no access to digital literacy education programs on how to use the digital economy, especially e-commerce in developing products. One of the challenges is the problem in using the online application to run the business. Closely, the low number of MSME actors in accessing on-line applications is mainly caused by internal and external factors, including the quality of human resources (HR) of business actors. This research aims to investigate the factors that influence the use of the digital economy including the use of e-commerce. The research was set during the pandemic in two Indonesian cities; Tangsel and Lombok. The analysis was conducted by using the Technology Acceptance Model (TAM) approach and the Theory of Planned Behavior Model as a planned behavior theory. The study pinpoints that in conducting the process of buying and selling transactions through e-commerce media, various considerations such as ease of use, and expediency as well as the existence of attitudes, norms, behavioral controls, are important things for users of the digital economy, including e-commerce, are the main factors to pay attention to. This study confirms the that behavioral control determines how a MSMEs actor maximize the use of the digital economy, and the level of mastering the advanced technology is the key factor. The finding of this research is recommended for the policy makers in the Ministry of Cooperatives & MSMEs in strategizing the development of micro scale of micro, small & medium enterprises to improve the national economy growth.